Optimization of Deep Neural Networks Using a Micro Genetic Algorithm - Ricardo Landa; David Tovias-Alanis; Gregorio Toscano (AI)
This work proposes the use of a micro genetic algorithm to optimize the architecture of fully connected layers in convolutional neural networks, with the aim of reducing model complexity without sacrificing performance. Our approach applies the paradigm of transfer learning, enabling training without the need for extensive datasets. A micro genetic algorithm requires fewer computational resources due to its reduced population size, while still preserving a substantial degree of the search capabilities found in algorithms with larger populations. By exploring different representations and objective functions, including classification accuracy, hidden neuron ratio, minimum redundancy, and maximum relevance for feature selection, eight algorithmic variants were developed, with six variants performing both hidden layers reduction and feature-selection tasks. Experimental results indicate that the proposed algorithm effectively reduces the architecture of the fully connected layers in the convolutional neural network. The variant achieving the best reduction used only 44% of the convolutional features in the input layer, and only 9.7% of neurons in the hidden layers, without negatively impacting (statistically confirmed) classification accuracy when compared to a network model based on a full reference architecture and a representative method from the literature.